Socio-Culturally Based Aqidah Akhlak Education to Prevent Student Hedonism - Anis Fadilatan Nafsi; Ikhwan Aziz Q; M Zainal Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The phenomenon of hedonistic lifestyles among adolescents is increasingly prevalent, including among students in the madrasah environment. This behavior is reflected in consumptive tendencies, wasteful use of pocket money, and following trends without considering needs and moral values. This condition poses a challenge for educational institutions in instilling moral and faith-based values that can shape students' character. The purpose of this study is to analyze the role of socio-culturally based moral and faith education in preventing hedonistic behavior among students at MA Ma'arif 02 Seputih Surabaya. This research is a field study employing data collection techniques through a combination of methods (observation, interviews, and documentation). For data analysis, the researcher used a qualitative approach. Based on the analysis of the data discussed, this study reveals that socio-culturally based moral and faith education plays a role in preventing hedonistic behavior through: Spiritual reinforcement through habitual worship practices, internalization of zuhud (asceticism) and qana'ah (contentment) values through local wisdom, strengthening self-control through teacher role modeling, and developing social awareness through religious activities.This approach fosters simplicity, responsibility, and moral awareness in students, thereby minimizing consumptive behavior.